Az élethez való jog néhány jogelméleti kérdéséről - Vörös, Judit (Debreceni Jogi Műhely, 2013)
Nowadays in vitro fertilisation raises relevant controversies at the point of view of jurisprudence as well. The distinct approximations of in vitro embryos, such as to be considered as personae or objects, are also resources of several theoretical and pragmatical questions. It is essential to give a compendious summary about what kind of jurisprudental environment had been contributed to the intrumental comprehension of human embryos too, otherwise it is difficult to understand the scientific quandaries connected to the subject correctly. Merely thereafter the international and the Hungarian regulation of in vitro embryo’s status seems to able to be dissected, in particular the case-law of the Hungarian Constitutional Court related to the right to life and the constitutional funds of the oncurrent re-regulation in our country.